Padlet as a Digital Tool to Improve Students Motivation and Writing Abilities in Grade 7 - Althaf Maulana; Gusti Nur Hafifah; Nur Afifah (PROCEEDING UMSURABAYA, 2026)
This study aims to improve the writing abilities and learning motivation of seventh-grade students of the Junior High School in Surabaya through the use of Padlet as a technology-based learning media in the Project-Based Learning (PjBL) model. This study uses a Classroom Action Research (CAR) design with a cycle approach consisting of planning, action implementation, observation, and reflection stages. The subjects of the study were 31 students of class VII A. Data were collected through pre-tests and post-tests as well as classroom observation. The results showed that the average score of students increased from 69.3 in the pre-test to 78.3 in the post-test. The percentage of learning completion also increased from 51.6% to 87.1% in just one cycle. In addition to improving writing abilities, the integration of Padlet also creates a collaborative, interactive, and enjoyable learning environment that encourages students to be more active in expressing their ideas in writing. The Culturally Responsive Teaching (CRT) approach used in the learning process has also proven effective in increasing the relevance of the material to students' backgrounds, thus triggering their intrinsic motivation in writing. These findings indicate that the integration of technology through Padlet in the PjBL model, supported by the CRT approach, is not only able to improve students' writing abilities but also motivates them to be more actively involved in the learning process. Therefore, the use of Padlet is recommended as an innovative learning strategy to improve students' 21st-century abilities, especially in writing.